Recent developments in behavioral economics - Maital, Shlomo (Cheltenham: Edward Elgar, 2007)
This volume treats behavioral economics by studying the historical origins, methodologies for researching behavior and decision choices, rational choice in childhood, present - future choice saving, risk, social norms and culture etc.
Includes index.
Includes bibliographical references and index
osc 12/02/14
Loans
Keywords: Economics -- Psychological aspects